2006
DOI: 10.1021/jp0549834
|View full text |Cite
|
Sign up to set email alerts
|

CH-Stretching Overtone Spectra of cis- and trans-1,3-Pentadiene

Abstract: The room-temperature vapor-phase overtone spectra of cis- and trans-1,3-pentadiene (piperylene) have been recorded in the 5000-17500 cm(-1) region with the use of conventional and intracavity laser photoacoustic spectroscopy. The presence of five nonequivalent olefinic CH bonds and one methyl group in each molecule complicates assignment of the spectra. We have used a harmonically coupled anharmonic oscillator local mode model with one oscillator for each of the nonequivalent CH bonds to calculate the CH-stret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Analysis of the experimental spectra yielded oscillator strengths, f, obtained using the following equation 64,65…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the experimental spectra yielded oscillator strengths, f, obtained using the following equation 64,65…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the experimental spectra yielded oscillator strengths, f , obtained using the following equation , f = 2.6935 × 10 9 ( K 1 Torr m cm ) T p l A ( ) d where T is the temperature of the sample, p is the sample pressure in the cell, l is the path length, and A is the absorbance (log 10 ). Because the photoacoustic signal is proportional to absorbance with an unknown constant, absolute absorbance data from the photoacoustic spectra cannot be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the LMM parameters provide bond-specific information somewhat different from that available from normal-mode spectra. The CH stretching higher overtones ( n = 2–6) of alkenes , and naphthalene in the gas phase have been measured and compared with the high-level theoretical calculations of anharmonic spectra. It was shown that the experimental spectra in the higher overtone region are well reproduced by a simple Morse oscillator LMM.…”
Section: Applications Of Nir Spectroscopymentioning
confidence: 99%
“…Absolute oscillator strengths for C-H and O-H stretching overtone vibrations have been investigated using harmonically (HCAO) and anharmonically (ACAO) coupled anharmonic oscillator local mode models. 15,42,45,46,55,[114][115][116][117] Fewer studies have been done on N-H and S-H transitions. 46,[118][119][120][121] In Fig.…”
Section: Vibrational Overtone Initiated Atmospheric Photochemical Rea...mentioning
confidence: 99%